Competitive balance and match attendance in European rugby union leagues - Vincent Hogan; Patrick Massey; Shane Massey (University College Dublin, UCD School of Economics, 2012)
The paper analyses the impact of the relatively belated move to professionalism in Rugby Union. We use data on match attendance for 3,667 fixtures in European club Rugby over 15 seasons to estimate the effect of competitive balance on attendance. We find that (short- and medium-term) competitive balance has a large and statistically significant effect. However, this effect is smaller in magnitude than the effect brought about by the other aspects of the fixture with the strength of the home team being the single most important influence on attendances.
Keywords: D12; D21; L22; L23; L83; 330; Professional team sports; competitive balance; league structures; revenue sharing; salary caps; consumer demand